2001
DOI: 10.1111/0019-8676.00221
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Developments in Industrial Democracy

Abstract: The purpose of this article is to analyze recent developments in industrial democracy (worker participation in management) in a comparative perspective. To give the article focus, the period from the mid‐1980s onward is selected for analysis, and four countries (United States, Germany, United Kingdom, and Australia) are targeted for systematic examination. Developments in both indirect and direct participation are explained on the basis of elements in the models that we present. Three particularly strong concl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 22 publications
(28 reference statements)
1
39
0
2
Order By: Relevance
“…Union involvement in the design and implementation of work teams, union demands for greater democracy within work teams and better working conditions, and union support for teams and team leaders are the factors most strongly associated with the spread of democracy within work teams and enhanced worker well-being [Gollan and Markey, (2001), pp.324 and 328;Huzzard et al, 2004;Knudsen et al, 2011;Vidal, 2007]. On balance, industrial democracy, which combines direct and representative democracy in a relationship of mutual support, is an effective framework for analysing work teams (Frege, 2007;Poole et al, 2001;Knudsen et al, 2011;Lansbury, 2009). …”
Section: Teamwork Democratisation and Union Rolementioning
confidence: 99%
“…Union involvement in the design and implementation of work teams, union demands for greater democracy within work teams and better working conditions, and union support for teams and team leaders are the factors most strongly associated with the spread of democracy within work teams and enhanced worker well-being [Gollan and Markey, (2001), pp.324 and 328;Huzzard et al, 2004;Knudsen et al, 2011;Vidal, 2007]. On balance, industrial democracy, which combines direct and representative democracy in a relationship of mutual support, is an effective framework for analysing work teams (Frege, 2007;Poole et al, 2001;Knudsen et al, 2011;Lansbury, 2009). …”
Section: Teamwork Democratisation and Union Rolementioning
confidence: 99%
“…Pues bien, esta democracia social que se va extendiendo a todos los niveles, constituye una de las causas principales que desembocan en la democracia económica, característica de las sociedades tecnológicas, y cuya máxima representación se alcanza a través de los diversos mecanismos de participación de los trabajadores en las empresas (Divar, 1990;Tezanos, 1987) con los que se pretende superar la "experiencia social escindida" (Tezanos, 1987, pag.21) qu e -548-Intangible Capital -http://dx.doi.org/10.3926/ic.652 supone para la clase trabajadora, por una parte, tener reconocido el derecho a la participación en la organización política, y por otra, carecer totalmente del más mínimo derecho a la participación en la organización de la empresa, lo que convierte esta segunda realidad en mucho más compleja de entender y mucho más dura de aceptar. La influencia de este proceso de democratización en las propias personas directivas también se ha identificado como una causa favorable a la participación (Poole, Lansbury & Wailes, 2001). …”
Section: Las Organizaciones Participativas Y El Cooperativismounclassified
“…Esta disección en los niveles de participación determinará también los diferentes efectos que ésta producirá en una empresa en función de cuál sea su nivel de aplicación real, ya que existen múltiples modelos en que la participación puede llevarse a cabo (Strauss & Rosenstein, 1970;Logue & Yates, 2005;Gollan, 2005;Gollan & Patmore, 2002;Poole et al, 2001, Lawler, 1996 así como múltiples variables que pueden determinar el nivel de participación real en una organización (Albizu et al, 2005).…”
Section: Las Organizaciones Participativas Y El Cooperativismounclassified
“…Reflecting on this situation, Poole et al (2001) developed a ''multivariate explanatory approach'' to analyze the many variables that contribute to campaign success. Here, this approach has been adapted to focus on the standing and legitimacy of the NGOs, the influence of the Government, and the ''institutional forces'' that influence the development of government policy.…”
mentioning
confidence: 99%
“…Here, this approach has been adapted to focus on the standing and legitimacy of the NGOs, the influence of the Government, and the ''institutional forces'' that influence the development of government policy. Poole et al (2001) recognized this approach often results in complex patterns, but suggested it provides a more accurate reflection of a situation.…”
mentioning
confidence: 99%